2005
DOI: 10.1007/s00420-004-0590-6
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes as occupational and environmental respiratory sensitisers

Abstract: A literature review shows that airborne enzymes occurring in the general environment and in purified form in industrial production have a high allergenic potential to the airways, causing rhinitis, conjunctivitis and asthma. It can be assumed that this also applies to the increasing number of enzymes manufactured by the cloning of fast-growing genetically engineered microorganisms. Cross-sectional studies demonstrate exposure-response relations for IgE-mediated sensitisation and airway disorders. Atopic indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
(33 reference statements)
1
35
0
Order By: Relevance
“…Many other high-molecular-weight allergens can induce IgE-mediated rhinitis and asthma: agricultural mites (339-342, 347, 348, 350, 351), coffee beans (598), proteolytic enzymes (515,599,600), other enzymes (601,602), insect dust (577); plants and flowers (603,604).…”
Section: Other Mitesmentioning
confidence: 99%
“…Many other high-molecular-weight allergens can induce IgE-mediated rhinitis and asthma: agricultural mites (339-342, 347, 348, 350, 351), coffee beans (598), proteolytic enzymes (515,599,600), other enzymes (601,602), insect dust (577); plants and flowers (603,604).…”
Section: Other Mitesmentioning
confidence: 99%
“…A previous study found that there is trypsin and trypsin-like enzyme activity in extracted tissue samples from crustaceans (Sun and Lopata 2010), but there are no previous publications that have quantified the level of airborne trypsin activity during seafood processing. Trypsin is a common serine protease enzyme and inhaled by workers may have an immunological or non-immunological effect on the lungs (Sun and Lopata 2010;Baur 2005;Florsheim et al 2015;Madsen et al 2015). Optimal conditions for several crustacean trypsins are around 40˚C and pH6, which is close to the physiological conditions found in human lungs (Sun and Lopata 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Trypsin exposure is linked to innate inflammatory responses in cell models and is also suspected to play a role in allergy, including seafood allergies (Sun and Lopata 2010;Baur 2005;Larsen et al 2008). King crab trypsin has been shown to be a potent stimulator of protease-activated receptors linked to inflammatory reactions in airway cell models (Larsen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise in humans, exogenous enzymes like proteases from molds and mites furthermore as industry-related proteases, celluloses, and lipases have substance characteristics [15][16][17][18][19]. Environmental pollutants like cigarette smoke could more increase the substance properties of antigens: mice eupneic OA along with cigarette smoke exhibit high OA-specific immune globulin levels (representative of atopy) and distinct eosinophil-and secretion cell-enriched airway inflammation on airway challenge with nebulized OA [20]. This observation might offer a mechanistic basis for the notion that smoking may be a risk issue for respiratory disease development [21].…”
Section: Role Of Danger-associated Signal In Allergic Sensitizationmentioning
confidence: 99%